A Paradigm Shift: Supporting the Multidimensional Identities of Black Male Youth. Issue 2 (2nd April 2020) - Vereen, Linwood G.; Giovannetti, Marcelle R.; Bohecker, Lynn
ABSTRACT: Black male youth are poorly represented in the counseling literature. There is a focus on development from a deficit model and lack of attention to their complex and multidimensional identities. In addition, popular media invariably portray Black male youth through a myopic lens as needing to overcome a litany of challenges and struggles. The purpose of this article is to begin to combat this myopic view. This article further explores the notion of listening to learn from the voices of Black male youth prior to implementing group work practices. Implications for group work practice are provided.